Tumor microenvironmental 15‐PGDH depletion promotes fibrotic tumor formation and angiogenesis in pancreatic cancer. Issue 10 (23rd August 2022) - Bu, Luke; Yonemura, Atsuko; Yasuda‐Yoshihara, Noriko; Uchihara, Tomoyuki; Ismagulov, Galym; Takasugi, Sanae; Yasuda, Tadahito; Okamoto, Yuya; Kitamura, Fumimasa; Akiyama, Takahiko; Arima, Kota; Itoyama, Rumi; et al.
Abstract: The arachidonic acid cascade is a major inflammatory pathway that produces prostaglandin E2 (PGE2). Although inhibition of 15‐hydroxyprostaglandin dehydrogenase (15‐PGDH) is reported to lead to PGE2 accumulation, the role of 15‐PGDH expression in the tumor microenvironment remains unclear. We utilized Panc02 murine pancreatic cancer cells for orthotopic transplantation into wild‐type and 15‐pgdh +/− mice and found that 15‐pgdh depletion in the tumor microenvironment leads to enhanced tumorigenesis accompanied by an increase in cancer‐associated fibroblasts (CAFs) and the promotion of fibrosis. The fibrotic tumor microenvironment is widely considered to be hypovascular; however, we found that the angiogenesis level is maintained in 15‐pgdh +/− mice, and these changes were also observed in a genetically engineered PDAC mouse model. Further confirmation revealed that fibroblast growth factor 1 (FGF1) is secreted by pancreatic cancer cells after PGE2 stimulation, consequently promoting CAF proliferation and vascular endothelial growth factor A (VEGFA) expression in the tumor microenvironment. Finally, in 15‐pgdh +/− Acta2‐TK mice, depletion of fibroblasts inhibited angiogenesis and cancer cell viability in orthotopically transplanted tumors. These findings highlighted the role of 15‐pgdh downregulation in enhancing PGE2 accumulation in the pancreatic tumor microenvironment and in subsequently maintaining the angiogenesis level in fibrotic tumors along with CAF expansion. Abstract : Depletion of 15‐PGDH remodelling tumor microenvironment by promoting firosis and angiogenesis via the upregulation of FGF1 and VEGF.